Quality in Laboratory Hemostasis and Thrombosis - Kitchen, Steve; Olson, John D; Preston, F. Eric (John Wiley & Sons, Incorporated, 2013)
The hemostasis laboratory has a vital role in the diagnosis and management of patients with familial and acquired hemorrhagic and thrombotic disorders. Rapid changes in the number and complexity of tests in this discipline have presented challenges for laboratories, as they develop quality programs for the oversight of this testing. Quality in Laboratory Hemostasis and Thrombosis has been completely revised and updated to reflect the changing process of managing quality. The second edition provides information on all aspects of testing, from pre-analytic to analytic and result reporting, in addition to external quality assurance. Chapters throughout the book include the development of global guidelines for methods, as well as the preparation of international standard plasmas and reagents. Designed to capture the elements of quality at all levels of the practice of laboratory hemostasis and thrombosis, this book will guide the reader through the development of a quality program to support all activities in the hemostasis laboratory, both simple and complex.